(untitled) (Research, Society and Development, 2021)
Identify the actions of nurses in Primary Health Care for the prevention and early detection of breast cancer. Integrative review conducted in three databases using the descriptors Nursing in Primary Care, Oncology Nursing, and Breast Neoplasms, from which, at the end of the search, a total number of 15 eligible articles were obtained.Over the years, the Single Health System (SUS) has walked positively, improving the quality of care and guiding the professional nurse for better care in the workplace, requiring skills such as providing health care from the moment of prevention, diagnosis, treatment, rehabilitation, and palliative care. The highlighted typologies were Nursing in Primary Health Care, which is the nurse’s action at the SUS entrance door, and Breast Cancer Prevention in UBS, which is responsible for the quality of life and longevity of the enrolled population. The really effective fight against breast cancer depends on many factors, and it is worth mentioning the work of nurses in the prevention and maintenance of health.